High throughput resistance phenotyping of banana (Musa spp.) against Radopholus similis - Kisitu, J.; Saikai, K.K.; Coyne, D.; Kanaabi, R.; Kisaakye, J.; Swennen, R.; Nakato, G.V. (2025)
A high throughput in vitro screening method for phenotyping banana resistance to Radopholus similis was developed and validated using sand-MS media. The reproduction factor of R. similis showed a similar trend under in vitro and screenhouse conditions. The in vitro method proved sensitive and cost-effective for early-stage resistance screening, which favored higher nematode reproduction than in pots in the screenhouse. The in vitro method complements screenhouse screening but enables a higher throughput with a shorter turnaround time, accelerating phenotyping and enabling more rapid assessment of banana genotypes for breeding programs. Strangely, some genotypes were susceptible under in vitro but resistant under screenhouse conditions, and vice versa. Consequently, additional methods may be required, such as root necrosis scores, to validate resistance. However, this study provides the first in vitro-based demonstration of phenotyping for nematode resistance using modified sand-MS media. The modified sand-MS media appeared to provide a better environment for root development and pathogen interactions compared to gelrite and agar. By integrating both in vitro and screenhouse methods, banana breeding programs can accelerate the identification of resistant genotypes, while ensuring rigorous validation.